2021
DOI: 10.1523/jneurosci.1682-20.2020
|View full text |Cite
|
Sign up to set email alerts
|

Motor Interference, But Not Sensory Interference, Increases Midfrontal Theta Activity and Brain Synchronization during Reactive Control

Abstract: Cognitive control helps us to overcome task interference in challenging situations. Resolving conflicts because of interfering influences is believed to rely on midfrontal theta oscillations. However, different sources of interference necessitate different types of control. Attentional control is needed to suppress salient distractors. Motor control is needed to suppress goal-incompatible action impulses. While previous studies mostly studied the additive effects of attentional and motor conflicts, we independ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 74 publications
3
6
1
Order By: Relevance
“…It has been described as a driver of awareness, constantly receiving feedback information from interconnected networks ( Craig, 2009 ), as the ventral attentional network, which is functionally related to error awareness ( Klein et al, 2013 ). Thus, the link between a decreased theta activity and a greater probability of erroneous outcomes reported both in our data and in previous studies ( Cohen and Donner, 2013 ; Atchley et al, 2017 ; van Noordt et al, 2017 ; Kaiser and Schütz-Bosbach, 2021 ), might be explained by the reduced feedback from different networks to the anterior insula. It possibly highlights diminished attention and poor coordination of neural processing required for an efficient response ( White et al, 2013 ; Wallis et al, 2015 ; de Vries et al, 2020 ).…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…It has been described as a driver of awareness, constantly receiving feedback information from interconnected networks ( Craig, 2009 ), as the ventral attentional network, which is functionally related to error awareness ( Klein et al, 2013 ). Thus, the link between a decreased theta activity and a greater probability of erroneous outcomes reported both in our data and in previous studies ( Cohen and Donner, 2013 ; Atchley et al, 2017 ; van Noordt et al, 2017 ; Kaiser and Schütz-Bosbach, 2021 ), might be explained by the reduced feedback from different networks to the anterior insula. It possibly highlights diminished attention and poor coordination of neural processing required for an efficient response ( White et al, 2013 ; Wallis et al, 2015 ; de Vries et al, 2020 ).…”
Section: Discussionsupporting
confidence: 69%
“…Recent studies have found evidence for distinct midfrontal theta inputs ( Töllner et al, 2017 ; Zuure et al, 2020 ), thus suggesting rather than a unitary neural mechanism of cognitive control ( Cavanagh et al, 2012 ; Cavanagh and Frank, 2014 ; Kaiser et al, 2019 ; Duprez et al, 2020 ), it might reflect different underlying neural processes depending on the task context. In line with this, Kaiser and Schütz-Bosbach (2021) found that pre-response theta is linked to synchronization of task-relevant brain areas and demonstrated domain-specific effects of theta power and connectivity. Their findings highlighted the need for further dissociation between general and domain-specific neural effects during different types of behavioral interactions as an important step for the understanding of the midfrontal theta role neural in cognitive control.…”
Section: Introductionsupporting
confidence: 62%
See 1 more Smart Citation
“…In this context, it has been recently proposed that theta coherence between the medial prefrontal cortex (mPFC) and the anterior cingulate cortex (ACC) predicts the speed and the task performance and represents a crucial mechanism for a performing cognitive control (Myers et al, 2021). In the same way, numerous studies (Helfrich et al, 2019;Kaiser and Schütz-Bosbach, 2021) have suggested that the theta oscillation assumed a general control mechanism, exerting a top-down control during both sensorimotor interference and goal behavior. Gärtner et al (2014) demonstrated the existence of a close link between working memory performance and the theta oscillation (4-8 Hz) which were both reduced under stress conditions.…”
Section: The Individual Alpha Peak Frequency Was Not Modified By Reba...mentioning
confidence: 98%
“…Action regulation in this context refers to an adjustment of ongoing behavior in order to improve one's chances to successfully reach a goal. Successful action regulation commonly depends on voluntary exertion of cognitive control mechanisms to override goal-incompatible behavioral tendencies (van de Vijver et al, 2011 ; Gratton et al, 2017 ; Kaiser and Schütz-Bosbach, 2019 , 2021 ). Concerning the role of affective processing, we specifically focus here on the processing of positive and negative performance feedback during tasks which necessitate action regulation.…”
Section: The Role Of Sense Of Agency and Affective Processing For Action Regulationmentioning
confidence: 99%